2013
DOI: 10.1007/s00266-012-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

The “Dermal Cage”: A Modification of the Inferior Pedicle Breast Reduction

Abstract: Abstract:In spite of more recent techniques for breast reduction, the inferior pedicle technique has proven to be enduring being a still a very popular option in the plastic surgeons armamentarium despite certain shortcomings. This utility is especially so for the treatment of large breasts with a long sternal notch to nipple distance. The modifications we describe in this article, overcome some of the main drawbacks of the standard inferior pedicle technique, and is particularly effective when used with appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Drawbacks of the technique include the tendency to develop pseudoptosis (or 'bottoming out'), tedious de-epithelialisation, poor or inadequate projection, upward NAC rotation, and tension at the inverted T-junction. Many modifications have been proposed to alleviate or avoid these issues [2][3][4][5]7,[11][12][13][14][15]. Most of these modifications are based on plication and fixation of the pedicle on the pectoral fascia via dermal flaps extending from it [2,4,7,[13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Drawbacks of the technique include the tendency to develop pseudoptosis (or 'bottoming out'), tedious de-epithelialisation, poor or inadequate projection, upward NAC rotation, and tension at the inverted T-junction. Many modifications have been proposed to alleviate or avoid these issues [2][3][4][5]7,[11][12][13][14][15]. Most of these modifications are based on plication and fixation of the pedicle on the pectoral fascia via dermal flaps extending from it [2,4,7,[13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Echo et al [4] reported better medial fullness and NAC projection with a horizontal dermal suspension sling and plication of the dermal flaps. Based on a similar approach, Zic et al [2] published their technique involving support of the pedicle in multiple directions by a 'dermal cage' they fashioned. As a modification of McKissock's technique, Yazici et al [12] reported plication of the vertical pedicle in the superior and inferior directions, thus fashioning a new breast meridian, and suturing the medial and lateral pillars to it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inferior pedicle with inverted T scar reduction Mammaplasty, one of the most regularly performed technique [8], was first introduced by Riberio [9] followed by many modifications. These include the use of synthetic mesh [10,11] suspending the pedicle [12,13] and a superficial fascial system suspension [14] thus becoming less reliant upon the skin brassiere.…”
mentioning
confidence: 99%